THE EFFECT OF NEURAL CONTROL EXERCISES IN IMPROVING MOTOR PERFORMANCE IN HANDBALL PLAYERS - Naji, Nasreen Hassan; Kamil, Naseer Ahmed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
Some handball players suffer from a defect in the ability to perform passes smoothly and with controlled movement with directed balance when executing skills, due to weakness in movement control, which causes a defect in their performance in matches. The aim of the research was to identify the effect of neural control exercises in improving motor performance in handball players. The researchers used the single-group experimental method to suit the nature of the research procedures. The sample included (12) players who represented the University of Kufa handball team for the academic year (2024-2025). After applying the tests under study, the data was collected, processed statistically, displayed and analyzed, and the most important conclusions were reached:The results showed that the neural control exercises enhanced the variables under study in handball players, through improving their motor performance.The results showed that the neural control exercises improved the players' performance in the skills of passing and shooting in handball players.